Analysis of the Influence of it Affordance in Live Commerce on Tiktok Shop Applications on Purchase Decisions in DKI Jakarta - Zhafirah Lavinia; Eko Budi Santoso (International Journal Labs, 2026)
The rapid development of digital technology and social media has driven the transformation of electronic commerce models through the adoption of Live commerce. TikTok Shop is one of the platforms that integrates the live streaming feature as a medium for interaction and transactions between sellers and consumers. However, the effectiveness of technological features in Live commerce is still influenced by the psychological responses of consumers during the shopping process. This study aims to analyze the effect of IT affordance, which consists of visibility, metavoicing, and shopping guidance, on purchasing decisions in TikTok Shop Live commerce in the DKI Jakarta province, with perceptions of comfort and consumer confidence as mediating variables. This study uses a quantitative approach with a survey method involving TikTok Shop consumers in DKI Jakarta who have made purchases through the Live commerce feature. Primary data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results showed that all dimensions of IT affordance significantly affect perceptions of comfort and consumer confidence. Furthermore, perceptions of comfort and consumer confidence have been shown to significantly influence purchasing decisions and act as mediating variables in the relationship between IT affordance and purchasing decisions. Within the Stimulus–Organism–Response (S-O-R) framework, IT affordance serves as the stimulus, perceptions of consumer comfort and confidence as the organism, and purchase decision as the response.